A study on machinability of Al Si7 Mg2/SiCp metal matrix composite - Kilickap, Erol; Inan, Ali (My University, 2006)
This paper presents the result of an experimental investigation on the machinability of silicon carbide (SiC) particulate Al Si7 Mg2 Metal Matrix Composite (MMC) during turning using fixed WC insert (TiN coated and uncoated). Al Si7 Mg2 alloy composites contain various particle sizes (10-32 ?m) of 15 wt.% SiCp were prepared by squeeze casting method. Optical microscopic examination, hardness, density, tensile strength and impact toughness measurement were carried out. The influence of machining parameters, for example, cutting speed, feed and depth of cut on tool wear and surface roughness were investigated during the experimentation. Test results show BUE is formed during machining of Al Si7 Mg2/SiCp-MMC at low cutting speed, low feed and high depth of cut. In without coolant turning condition, the tool wear was mainly affected by cutting speed, increased with higher cutting speed. Meanwhile, surface roughness was influenced with combination of feed and cutting speed. © 2006 Inderscience Enterprises Ltd.
Keywords: machining; Metal Matrix Composite (MMC); surface roughness; tool wear